Investigating the Impact of Anthropogenic Change on Soil Microbiome Functioning and Crop Health - McEntagart, Jake (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Microbiology, 2025)
Anthropogenic change poses significant challenges for society today. Soil microbial communities are under constant anthropogenic stress from pollution, rising climates, pesticide use, and deforestation to name a few. We have little idea how anthropogenic stress shapes soil communities, and the impact that stress can have on soil community functioning. This study examines the impact of fungicide and temperature stress, individually and in combination, on the phenotypes of soil communities. Evaluations included their phenotypic adaptation to these stressors, virulence, antibiotic resistance, and their capacity to enhance plant growth and defence mechanisms. Results revealed that isolates from soil communities evolved under fungicide stress exhibited heightened adaptation to both fungicide and temperature stress compared to those from the stress-free control and temperature-only evolved communities. Virulence assays using wax moth larvae (Galleria mellonella) indicated that fungicide-evolved soil communities displayed reduced virulence towards their host compared to ancestral or control evolved communities. Conversely, isolates from the increasing temperature evolved communities predominantly showed greater antibiotic susceptibility compared to evolutionary control isolates. Furthermore, fungicide-evolved communities conferred improved barley (Hordeum vulgare) shoot height after 20 days. Together, this study highlights that anthropogenic stressors can in some cases markedly affect the phenotype of soil communities, with impacts for crop growth, antimicrobial resistance, and virulence. Further work should determine how anthropogenic stress affects crop production, indirectly, via changes to the soil microbiome.
APPROVED
Keywords: Anthropogenic change; Anthropogenic stressors; Fungicide; Soil Community; Soil microbiome; Evolution; Crop growth; Crop Defence; Aphids; Non-targets